Pengaruh Kualitas Layanan, Kemudahan Penggunaan dan Harga Produk Terhadap Keputusan Pembelian di Shopee - Habib Fajar Aditya; Rayhan Gunaningrat (Global Leadership Organizational Research in Management, 2024)
Consumers want to be respected throughout the purchasing process until after sales. Service quality is something that is important for the industry to pay attention to because it has an impact on consumers who want to shop. Ease of use, such as ease of navigation and collection of information, makes it easier for consumers to make purchases. Price determines consumers' purchasing decisions. Price determines how consumers search for products and compare prices before making a final decision. This research uses a quantitative approach in its research methodology. The information used in this research is essential information. Main information was collected through an online questionnaire distributed to Shopee consumers in the Greater Solo area via Google Form and distributed via social media platforms. The survey contains questions that are assessed using a Likert Scale of 1 to 5. Data processing uses the SPSS version 25 program. To expect a questionnaire that may not be completed, an example of a decision size is 108 respondents in this review. The results of the findings can be summarized as follows: service quality has a significance value of 0.000<0.05, ease of use has a significance value of 0.042<0.05, and product price has a significance value of 0.000<0.05. As a result, all variables have a significant impact significant impact on consumers' decisions regarding which products to buy. There is a significant impact on the quality of service, ease of use, and price of products available on the Shopee platform.